Characterization of Xylanase Streptomyces spp. SKK1-8 - MERYANDINI, ANJA; HENDARWIN, TRIO; SAPRUDIN, DEDEN; LESTARI, YULIN (HAYATI Journal of Biosciences, 2009)
Streptomyces spp. SKK1-8 producing xylanase was isolated from soil sample from Sukabumi West Java. The xylanase have an optimum condition at pH 6 and 50 0C. Addition of 5 mM Cu2+ decreased the xylanase activity up to about 77%, whereas not by other cations. The xylanase was stable at 3 0C for 48 hours, and the enzyme half lifetime was 1 hour 45 minute at 50 0C. This xylanase showed the highest activity on oatspelt xylan, and their molecular masses were estimated approximately 16.80, 15.21, and 13.86 kDa. HPLC analysis showed that xylosa and arabinosa were the main hydrolytic product of birchwood xylan. Key words: xilanase, Streptomyces spp., characterization, zymogram and SDS-PAGE, stability